2022
DOI: 10.3390/app12073333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rounded and Hunched Shoulder Postures on Myotonometric Measurements of Upper Body Muscles in Sedentary Workers

Abstract: Background: Shoulder pain is prominent among sedentary employees who make motions of the upper limbs on a regular basis. Rounded shoulder posture (RSP) and hunched shoulder posture (HSP) are the most common clinical postural misalignments. These causes the spine to bend and raise tension on the nerve roots, which has a negative impact on upper-extremity muscular strength and function. Therefore, this study was carried out to investigate the effect of RSP and HSP on the mechanical parameters of the upper body m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This device uses silent EMG signals to detect these changes. (6,7) This device has been validated in assessing wrist stiffness and upper and lower body muscles. See Figure 1 anatomical sites.…”
Section: Discussionmentioning
confidence: 99%
“…This device uses silent EMG signals to detect these changes. (6,7) This device has been validated in assessing wrist stiffness and upper and lower body muscles. See Figure 1 anatomical sites.…”
Section: Discussionmentioning
confidence: 99%
“…Tension relaxation time reflects the duration of the muscle’s recovery process [ 22 , 23 ]. It is a measure of the time required for the muscle to return to its initial state.…”
Section: Introductionmentioning
confidence: 99%
“…It is a measure of the time required for the muscle to return to its initial state. On the other hand, muscle creep is defined as the gradual stretching of the muscle under a constant tensile stress [ 20 , 23 ]. This phenomenon provides crucial information about the structural properties of the muscle and its response to sustained loading and contributes to a comprehensive understanding of its viscoelastic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, it presents advantages in providing information about the viscoelastic parameters of tissues through a noninvasive digital palpation technique. In this regard, some studies have reported applications of the Myoton instrument in occupational research, such as the increased muscle tone observed in the shoulder region of sedentary workers ( Guduru et al 2022 ). A study that employed myotonometry linked to ergonomic risks and forced postures in road construction workers was able to conclude the advantage of using muscle tone as a parameter in the study of fatigue associated with individuals with lower physical fitness ( Roja et al 2006 ).…”
Section: Introductionmentioning
confidence: 99%